Resepsie van 2 Makkabeërs 6:18-7:42 in 'n multi-kulturele Suid-Afrikaanse Protestantse gemeenskap - Jordaan, Pierre J. (Journal for semitics, 2013)
A sample investigation into how a multi-cultural Protestant South African community received the martyr texts in 2 Maccabees 6:31-7:42 provided interesting results. Various threats to their Christian faith were identified. A deep spiritual need emerged to make sense of troubling circumstances. In an attempt to address these problems the martyr texts of 2 Maccabees 6:31-7:42 were seen to be suitable. The research in this paper was undertaken without any expectation that we would reach any specific results. The spiritual need among this specific sample of a Protestant community in South Africa shows that it may be the right time for a fresh approach to the corpus of apocryphal books.